The Influence of Using Interactive Learning Videos Based on Inquiry on the Science Learning Outcomes of Grade IV Students of UPTD SD Negeri 67 Parepare - Muhammad Asrul Sultan; Nurul Mukhlisa; Mutmatul Amna Ruslan (International Journal of Education, Culture, and Society, 2026)
This study examined the effect of interactive learning videos on Grade IV students’ learning outcomes in Natural and Social Sciences (IPAS) at UPTD SD Negeri 67 Parepare. A quantitative approach was employed using a pre-experimental, one-group pretest–posttest design. The study population comprised 218 students enrolled at the school, while the sample consisted of one Grade IV class comprising 31 students. The participants received instruction using interactive learning videos during the IPAS learning process. Data were collected through learning-outcome tests administered before and after the intervention and analyzed using descriptive and inferential statistics. A paired-samples t test was conducted to determine whether students’ learning outcomes differed significantly between the pretest and posttest. The analysis produced a two-tailed significance value of p = .001, which was below the .05 significance threshold; therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted. These findings demonstrate a statistically significant difference in students’ learning outcomes following the use of interactive learning videos. Thus, interactive learning videos were associated with improved IPAS learning outcomes among the participating Grade IV students. The findings indicate that interactive learning videos can serve as a potentially effective instructional medium for supporting IPAS learning in elementary school settings, although the pre-experimental design limits the strength of causal inference.